ANESTESIA PARA CORREÇÃO DE SHUNT PORTOSSISTÊMICO: RELATO DE CASO - Campos Medeiros, Laura; Machado de Freitas, Ana Eduarda; Campos Duarte Florenzano, Giovanna; Gonçalves Penna Guedes dos Reis, Maria Antônia; Vignoli de Almeida, Ana Clara; de Souza Pimentel, Gabrielle; Antunes de Lima, Marcos Paulo (Sinapse Múltipla, 2023)
Nao há